2005
DOI: 10.1007/s10452-005-9002-6
|View full text |Cite
|
Sign up to set email alerts
|

Zooplankton of a flooded opencast sulphur mine

Abstract: The zooplankton community of a flooded opencast sulphur mine was investigated during two years. The complicated physical and chemical relationships in this water-filled pit caused an atypical plankton assemblage. At the time of the investigation 20 species of rotifers, 6 of Cladocera, and 8 species of Copepoda were found. A single Ostracod and Chaoborus flavicans were also noted in the samples. Usually the epilimnion was monopolised by rotifers whereas the hypolimnion had a more diversified assemblage of rotif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…Ecnomus tenellus and Polycentropus flavomaculatus) could have been caused by the lack of appropriate food, e.g. phyto-as well as zooplankton in Lake Piaseczno which is very scarce (Wilk-Woz´niak and _ Zurek 2006;_ Zurek 2006b). Among the macrophytes life conditions for fauna may be better than at the bottom of Lake Piaseczno and in this habitat the diversity of invertebrate communities may be higher (especially Coleoptera, Odonata and Gastropoda could be present).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Ecnomus tenellus and Polycentropus flavomaculatus) could have been caused by the lack of appropriate food, e.g. phyto-as well as zooplankton in Lake Piaseczno which is very scarce (Wilk-Woz´niak and _ Zurek 2006;_ Zurek 2006b). Among the macrophytes life conditions for fauna may be better than at the bottom of Lake Piaseczno and in this habitat the diversity of invertebrate communities may be higher (especially Coleoptera, Odonata and Gastropoda could be present).…”
Section: Discussionmentioning
confidence: 98%
“…Studies on such water bodies have concentrated mainly on water chemistry (Kostecki 1974;_ Zurek 2002;Galas 2003) and the possibilities of restoration of these postexploitation areas (Crains 1983;Puchalski 1985;Kennedy et al 1999;Gaydin and Zozula 2002). There has also been some research done on the zooplankton of such water bodies (Ejsmont-Karabin 1995;Wollmann et al 2000;S´lusarczyk 2003; _ Zurek 2006b) but studies on the benthic fauna have been less frequent (Canton and Ward 1981) and sometimes only a single taxonomic group was studied (Strzelec 1993;Dumnicka and Krodkiewska 2003;Krodkiewska 2003).…”
Section: Introductionmentioning
confidence: 98%
“…These particular ecosystems escape the attention of the investigators mostly because they are man-made, usually a result of surface mining gypsum, and consequently studies of the zooplankton of such areas are scarce (Kuznetsova & Bayanov 2001;Zurek 2006;Stanković et al 2010). The latter authors found that the gypsum karst lakes are unique ecosystems that can even have different community composition compared to other nearby karstic lakes.…”
Section: Introductionmentioning
confidence: 99%
“…The fact, that they were migrating within a diurnal circle, suggests that they must have a biological origin, however the depths of their occurrence (anoxic zone) exclude the possibility that they were fish. The only species encountered in biological samples ( _ Zurek 2006b) that are known to reflect sound were Chaoborus larvae (Eckmann 1998), so probably this thin layer was made of them. The studies of bottom fauna of lake Piaseczno (Dumnicka and Galas 2006) have shown that Chaoborus flavicans was abundant beginning from the 5 m station and its highest share was found at 10 m (57% of the total benthic Among the second group of targets much stronger scatterers of sound were present, they varied highly in size and were distributed randomly in the water column down to circa 10 m. There is no doubt that this category consisted of fish.…”
Section: Resultsmentioning
confidence: 99%
“…Complex hydrochemical and hydrobiological studies of the Piaseczno reservoir were carried out during 2000-2003 on the monthly basis. They included water chemistry (Frankiewicz andPucek 2006, _ Zurek 2006a), microbial activity (Mazurkiewicz and Bednarz 2004), sediments (Szarek- Gwiazda et al 2006), phyto-and zooplankton (Bucka and Wilk-Woz´niak 2006;_ Zurek 2006b), benthic fauna (Dumnicka and Galas 2006), and fish (Amirowicz 2004). These studies have shown that hard waters of strong salinity, high concentration of sulphur hydrogen near bottom and toxic effects of heavy metals create very specific conditions, which are unfavorable for biological life.…”
Section: Introductionmentioning
confidence: 99%